Experimental demonstration of a tunable photonic hook by a partially illuminated dielectric microcylinder - Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Liu Cheng-Yang; Wei Haode; Geynts Yu. E. Yury Elmarovich; Karabchevsky A. (2020, 2020)
Title screen